Situation and Future Management Study Guidelines in India (International Journal of Innovative Research in Engineering & Management, 2021)
The authors arrange a round table conversation to analyses and  discuss the most significant topics in Indian management  research. They worry about the inclination of Indian researchers  to unquestionably replicate western research and publication  practices. They advocate self-assured indigenous scholarship,  which meets the growth and educational requirements of the  country through the use of research frameworks and  methodologies as well as separately evolving curricula, content  and distribution methods, with the same rigor as the Western  models, at the IIM Bangalore in December 2011. Initially, the  critique of the so-called US study technique completely  disregards the subject. Obviously, the models must have climate,  but it is like the forest for trees being completely ignored. We only  begin to appreciate a player after they have won a worldwide  battle, irrespective of their number of competitions.
Keywords: Academy of Management; Business Schools; Indian Management; Management Research; Management Study